Of Reductionism and The Pendulum Swing: Connecting Toxicology and Human Health - Jaap C Hanekamp; Aalt Bast; Jan HJM Kwakman (SAGE Publishing, 2012)
In this contribution we will show that research in the field of toxicology, pharmacology and physiology is by and large characterised by a pendulum swing of which the amplitudes represent risks and benefits of exposure. As toxicology usually tests at higher levels than the populace routinely is exposed to, it reverts to mostly linear extrapolative models that express the risks of exposure, irrespective of dosages, only. However, as we will explicate in two examples, depending on dosages, it is less easy to separate risks and benefits than current toxicological research and regulatory efforts suggest. The same chemical compound, in the final analysis, is represented within the boundaries of both amplitudes, that is, show a biphasic, hormetic, dose-response. This is notable, as low-level exposures from the food-matrix are progressively more under scrutiny as a result of increasing analytical capabilities. Presence of low-level concentrations of a chemical in food is a regulatory proxy for human health, but in light of this hormetic dose-response objectionable. Moreover, given that an ecological threshold probably holds for most, if not all, man-made (bio)organic chemicals, these will be found to be naturally present in the food matrix. Both aspects require toxicology to close the gap between reductionist models and its extrapolative deficiencies and real-life scenarios.